FLANNEL BOARD DOLL: A MEDIA FOR LEARNING SPEAKING SKILLS FOR IBTIDAIYAH MADRASAH STUDENTS - Faizah, Maryam; Faizah, Putri Nur; Ulfa, Kulsum (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
Students need speaking skills to flow their ideas and thoughts. This study aims to develop a flannel board doll as an attractive and easy-to-use medium in the speaking learning process. The research was conducted using research and development methods using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The sample of this study was 23 students of class IV MI Roudlotul Ulum—data collection techniques using questionnaires, observation, and documentation. The results of the validation of media products meet the very valid criteria, with the value of the material validator being 90, the media design validator 90, and the learning expert validator 96. This media is equipped with various components that are easy to reach and use, so it gets a student response of 91.99% with the criteria very positive. Overall, using a flannel board doll in the speaking learning process can make it more engaging, provide a visual and tactile aid, and create a supportive and low-pressure environment for students to practice their speaking skills. By incorporating this medium into language learning activities, teachers can help improve their students' speaking skills and overall language proficiency. By using a flannel board, learning becomes more enjoyable and less monotonous.